MONITORING DAN CONTROLLING SINKRONISASI MIXER BETON POROS GANDA BERBASIS WIFI - nurcahya, Gigih Bagus Nurcahya; Hunaini, Fachrudin; Siswanto, Diky (Program Studi Teknik Elektro - Fakultas Teknik - Universitas Widyagama Malang, 2024)
Currently, the construction sector is increasingly developing among the community and business actors. There are various types or types of products on the market provided by concrete mixer manufacturers, such as double shaft mixers which are more efficient for mixing concrete mix so that homogeneity is well maintained. In concrete mixer products currently circulating on the market, there is no monitoring and controlling system for synchronization in the second gear-box rotation, which can prevent fatality damage from occurring. This research aims to create a synchronization monitoring and controlling tool for a double-axis concrete mixer to minimize damage due to use. In the second round, the gear box is corrected to maintain synchronization with the proximity sensor by sending information to the microcontroller which will be displayed on the LCD in the equipment operator's work area and can be accessed outside the operator's work area via a smartphone based on local WiFi network in the company area. If there is a difference in synchronization between the two gear-boxes, the microcontroller will automatically give a command to the relay to turn off the motor driving the two gear-boxes and it can be turned off directly via smartphone.